Psychological consequences of participation in combat - LADYHINA, Olena; SMYRNOV, Viacheslav (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Scientific publications focused on the unique psychological responses of combatants, as well as short-term and long-term effects of combat stress, were analyzed. The complex nature of psychological reactions to war stress was established, including both negative outcomes (moral trauma, post-traumatic stress disorder, depression, anxiety, addictive behaviors) and positive psychological phenomena (stress tolerance, resilience, post-traumatic growth). The prevalence of post-traumatic stress disorder among combatants is approximately 30%, and depressive and anxiety disorders are about 40%, highlighting the need for targeted psychological correction and prevention of stress-related mental disorders in combatants. Promising psychological phenomena that help counteract the destructive effects of combat stress include stress resistance, resilience, and post-traumatic growth, which can be cultivated through psychological training. Modern approaches to psychological correction of the adverse effects of combat stress include cognitive-behavioral approaches, psychoeducation, and socio-psychological adaptation of veterans. A prerequisite for the successful reintegration of combatants is overcoming stigmatization and creating a favorable social environment. Ukrainian combatants exhibit specific psychological characteristics: a combination of a high risk of moral trauma due to the need to fight on their own territory and numerous war crimes committed by the Russian occupiers, alongside a sense of mission, awareness of the importance of their social role as defenders of Ukraine, and a sense of cohesion and combat brotherhood. Future research should focus on in-depth exploration of psychological and psychopathological reactions to combat stress and their interrelationships, as well as the study of protective psychological phenomena that develop during combat experiences.
Keywords: combat stress; psychological response; posttraumatic disorders